Understanding factors that moderate the relationship between family poverty and depression among adolescents aged 10 to 16 years in rural districts of Balaka, Mchinji and Rumphi. - Munthali, Denis, Edmond (2022)
Adolescence is a critical stage in human development where physical, cognitive, and psychosocial growth takes place. Poverty is linked to adolescent depression. In Malawi, it is estimated that depression affects 16.9% of adolescents aged 10 to 16 years old. The objectives of the study were to assess the relationship between wealth index status and depression among adolescents and determine if this relationship is moderated by Adverse Childhood Experiences (ACEs) in the districts of Rumphi, Balaka and Mchinji. This study used cross-sectional secondary data collected in 2017 by Malawi Longitudinal Study of Families and Health-ACE (MLFSH-ACE). Logistic regression model was used to assess the relationship between wealth status and depression among adolescents. Odds ratios were generated to measure the association between wealth status and depression. ACEs factors were added to the model to test for moderation. The mean age in years was 13.2(±1.70) and 51% of the sample was female, 49% Male. School attendance among adolescents was at 91%. Adolescents from high wealth index households had lower odds of depression compared with adolescents from low wealth index households (aOR= 0.73, 95% CI: 0.56-0.95). Adolescents from a lower wealth index households have high odds of depression compared to adolescents from low wealth index households. In Developing countries, wealth index data can be used in identifying high risk households for adolescent’s depression and formulate appropriate interventions.